Identification of Staphylococcus aureus Bacteria on the Palms of Visitors to Panumbangan Health Center - Rivana Ariyadi; Putri Agnia Maulani; Undang Ruhimat; Rudy Hidana (Mukhtabar Journal of Medical Laboratory Technology, 2023)
Background & Objective: Hand hygiene is one of the efforts to prevent and control the spread of bacteria that can cause infectious diseases. Nosocomial infections can be caused by gram-positive bacteria, such as Staphylococcus aureus which is the most dominant bacterium causing skin and soft tissue infections. The purpose of this study was to determine the presence of Staphylococcus aureus bacteria in the palms of visitors to the Panumbangan Health Center. Method: This study is a descriptive observational study with a simple random sampling technique conducted from May to June 2022.  Respondents in this study were 20 health center visitors. Sampling was carried out at the Panumbangan Health Center and the examination was carried out at the STIKes Muhammadiyah Ciamis Bacteriology Laboratory. The measurement methods used were gram staining, media culture, and biochemical tests. The data obtained from the examination results were presented descriptively in tabular form and explained in narrative. Result: The results showed that 6 samples (30%) identified Staphylococcus aureus, 11 samples (55%) Staphylococcus epidermidis, and 3 samples (15%) suspected Streptococcus sp.   Conclusion: It can be concluded that 30% of Staphylococcus aureus, 55% of Staphylococcus epidermidis, and 15% of Streptococcus sp. were identified.